2015
DOI: 10.1016/j.jacc.2015.03.575
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Risk for Aortic Complications After Aortic Valve Replacement in Patients With Bicuspid Aortic Valve Versus Marfan Syndrome

Abstract: The much higher long-term rates of aortic complications after AVR observed in patients with Marfan syndrome compared with those with bicuspid aortic valves confirm that operative management of patients with bicuspid aortic valves should not be extrapolated from Marfan syndrome and support discrete treatment algorithms for these different clinical entities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 28 publications
6
59
0
2
Order By: Relevance
“…Among patients with MFS, AoD has been reported to occur in approximately 0.17% per year (7). A more recent study reported an increased risk among patients with MFS versus patients with BAV who underwent aortic valve replacement (14). However, this study excluded patients with TAA, leaving a substantial knowledge gap with respect to AoD risk after aortic grafting, as well as uncertainty with regard to diagnostic categorizations and follow-up events due to the fact that analysis was performed via a retrospective review of an administrative database.…”
Section: Discussionmentioning
confidence: 99%
“…Among patients with MFS, AoD has been reported to occur in approximately 0.17% per year (7). A more recent study reported an increased risk among patients with MFS versus patients with BAV who underwent aortic valve replacement (14). However, this study excluded patients with TAA, leaving a substantial knowledge gap with respect to AoD risk after aortic grafting, as well as uncertainty with regard to diagnostic categorizations and follow-up events due to the fact that analysis was performed via a retrospective review of an administrative database.…”
Section: Discussionmentioning
confidence: 99%
“…Itagaki and co-workers examined the natural history of aortopathy after aortic valve replacement (AVR) in a retrospective comparison of over 13,000 patients(31). The study very clearly showed that the risk of aortic complications in long-term follow-up for BAV patients was much closer to control patients than those with Marfan syndrome.…”
Section: Clinical Guidelines and The Evolving Approaches To Bicuspid mentioning
confidence: 99%
“…The assessment of hemodynamic flow in BAV patients shows distinct differences of the flow patterns compared to TAV patients (Keane et al, 2000). However, even after aortic valve replacement to correct the hemodynamics, some BAV patients still develop an ascending aortic aneurysm (Itagaki et al, 2015). Studies using aortic tissue from BAV patients have shown potential evidence of aortopathy of the aortic wall, including immature smooth muscle cells (SMCs) (Grewal et al, 2014b, Nkomo et al, 2003).…”
Section: Introductionmentioning
confidence: 99%